Reconstructing the trophic structure of Maastrichtian elasmobranch communities in Morocco using calcium isotopes - Alexandre Assemat; Sylvain Adnet; Jeremy E. Martin (Gondwana Research, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Exploring diet shifts and ecology in modern sharks using calcium isotopes and trace metal records of their teeth - Alexandre Assemat; Sylvain Adnet; Kani Bayez; Auguste Hassler; Florent Arnaud‐Godet; Frederik H. Mollen; Catherine Girard; Jeremy E. Martin (Journal of Fish Biology, 2024)
Sharks occupy all living environments of the marine realm as well as some freshwater systems. They display varied and flexible feeding behaviours, but understanding their diet remains challenging due to their elusive ecology and the invasiveness of stomach content analyses in regard of their threatened status. As a potential alternative, we discuss the variability in δ 44/42 Ca values recorded in the tooth enamel of size‐graded individuals belonging to three species of large sharks with distinct diets ( Isurus oxyrinchus , Hexanchus griseus and Carcharodon carcharias ). The preliminary results highlight shifts in diet linked to ontogeny ( I. oxyrinchus and H. griseus ) and spatial distribution ( C. carcharias ) characterizing feeding behaviour in these species at individual and population level. These outcomes agree with the results of traditional stomach analyses supporting that nontraditional stable isotopes thus represent new perspectives for the study of modern and extinct shark ecology. In addition, for the first time, the Sr/Ca elemental ratios measured in H. griseus reflect sexual differences that could be interpreted in terms of spatial segregation or physiological heterogeneities.

Shape diversity in conodont elements, a quantitative study using 3D topography - Alexandre Assemat; Ghislain Thiery; Thibaud Lieffroy; Catherine Girard (Marine Micropaleontology, 2023)